Case Study on the Mutual Influence of Simultaneous Construction of Adjacent Deep Foundation Pit with Cover-Excavation Reverse Method - Yong-Gang Xiao; Xiao-Min Liu; Xiao-Pei He; Chen Zheng; Qiang–Qiang Bai; Yu Zhang (Advances in Civil Engineering, 2024)
With the increasing utilization of urban underground space in densely populated cities, it is crucial to understand the interactive impact of the excavation sequence on the excavation group of foundation pits. The foundation pit of Tianta Station of Tianjin Metro Line 7 was adjacent to a deep foundation pit of an apartment, which provided a good case for the study of simultaneous excavation of foundation pits. In this paper, based on two deep foundation pit excavation projects, a finite element model was established to better understand the mutual influence of simultaneous foundation pit excavation. The responses of the two deep foundation pits under five different excavation sequences were investigated, including the horizontal displacement of the ground-connected wall and the displacement of the top of the wall, the settlement of the ground surface, and the supporting axial force of the basement floor slab. The position of the maximum horizontal displacement in different modes is the same, and the shape of the deformation curve was fish-bellied. When both pits B and C were excavated simultaneously, the surface settlement between adjacent pits was smaller than in other working conditions. Mode 5 is optimal among these five modes, in which not only the construction progress is the fastest but also the underground wall deformation and the ground settlement are relatively small. The findings and lessons learned from these two adjacent pits, both of which were constructed using the cap-and-reverse method, can help professionals optimize excavation design and construction, as well as performance prediction and control.